Lactate as a Predictor for Factors of Metabolic Syndrome in Males and Females with Overweight - Sulpar, Rebecca (East Carolina University, 2023)
Background: The prevalence of obesity has dramatically increased by more than 10% over the last twenty years. Risks of obesity include the development of metabolic syndrome (MetSyn) with concomitant development of conditions such as heart disease, stroke, type 2 diabetes, and some cancers. MetSyn is classified as having three of the following: a large waist circumference, hypertension, high blood sugar, high triglycerides, and dyslipidemia. Poor skeletal muscle metabolism is linked to obesity due to a low rate of fatty acid oxidation. Blood lactate is an indicator of oxidative capacity at rest and there is an inverse relationship between them. Elevated fasting plasma lactate levels in the body are present in obesity. Thus, lactate may be a precursor for obesity and metabolic diseases such as MetSyn in both males and females. Purpose: The purpose of this study was to determine if there is a relationship between blood lactate levels and its indices in men and women with overweight that has the potential to be used as a precursor for the development of MetSyn. Methods: Overweight subjects (n=29) with a body mass index (BMI) of 25.0-29.9 kg/m2 were screened for plasma lactate concentration. The subjects then returned for two additional visits. The first visit consisted of a DEXA scan, a 3-D body scan, and a maximal exercise test on a cycle ergometer. The participants returned for a Resting Metabolic Rate measurement. Results: Average fasting plasma lactate was 1.05 [plus-minus] 0.11 mmol/L. Plasma lactate was positively associated with factors of MetSyn such as total cholesterol (r=0.611, p=0.0004), triglyceride levels (r=0.49, p=0.007), LDL levels (r=0.582, p=0.0009), HOMA-IR values (r=0.626, p=0.0003), insulin levels (r=0.595, p=0.0007), android/gynoid ratio (r=0.396, p=0.034), and visceral adipose tissue (VAT) mass (r=0.672, p[less-than]0.0001). Other factors of MetSyn such as BMI, HDL, blood pressure (systolic and diastolic), and waist-to-hip ratio were not statistically significant. Conclusion: The results from the current study show that plasma lactate levels have positive relationships with factors of MetSyn. Analyzing plasma lactate values may help clinicians and future researchers predict the development of metabolic diseases such as metabolic syndrome.
Keywords: overweight; visceral adipose tissue; Blood lactate; Metabolic syndrome; Obesity--Prevention